Web interface-supported transmission risk assessment and cost-effectiveness analysis of postdonation screening: A global model applied to Ghana, Thailand, and the Netherlands - Van Hulst M. (2014)
Background: The goal of our research was to actively involve decision makers in the economic assessment of screening strategies in their region. This study attempted to accomplish this by providing an easy-to-use Web interface at http://www.bloodsafety.info that allows decision makers to adapt this model to local conditions. Study Design and Methods: The cost-effectiveness was compared of 1) adding antigen screening to antibody screening for hepatitis C virus (HCV) and human immunodeficiency virus (HIV); 2) adding nucleic acid amplification testing (NAT) on hepatitis B virus (HBV), HCV, and HIV in minipool (pool of 6 [MP6] and 24 [MP24]) to antibody screening and hepatitis B surface antigen (HBsAg) screening; and 3) individual-donation NAT on HBV, HCV, and HIV to antibody screening and HBsAg screening for Ghana, Thailand, and the Netherlands. Results: The combination of HCV antibody-antigen combination (combo) and HIV combo added to antibody screening in Ghana and Thailand was cost-effective according to the WHO criteria. MP24-NAT screening in Ghana was also cost-effective. MP24-NAT on HBV, HCV, and HIV was not cost-effective compared to the other screening strategies evaluated for the Netherlands. Large regional differences in cost-effectiveness were found for Thailand. Conclusion: The young transfusion recipient population of Ghana in combination with a high risk of viral transmission yields better cost-effectiveness for additional tests. The advanced age of the transfused population of the Netherlands and a small risk of viral transmission gives poor cost-effectiveness for more sensitive screening techniques. It was demonstrated that a global health economic model combined with a Web interface can provide easy access to risk assessment and cost-effectiveness analysis. ? 2009 American Association of Blood Banks.